The evolution of NB-IoT standard system and development of Internet of things industry - Yunzhou XIE (物联网学报)
Looking at the development of the Internet of things industry system,the birth of NB-IoT standard is the inevitable product of the development of the Internet of things.But in the development process of NB-IoT standard,it has gone through the business interests of the game,the market environment competition,and the secret contest of various groups,eventually forming a 3GPP international standard that people all accept.Different from the multi country and multi system pattern of wireless communication in the past,NB-IoT is a globally unified Internet of things wireless communication network.With the freeze of the Rel-13 version and the iterative evolution of the Rel-14 and Rel-15 versions,NB-IoT technology will also be the basis for the future 5G Internet of things standard system.From the perspective of the development of the whole pattern,the NB-IoT standard will be more suitable for the application scenarios of the Internet of things.The evolution of NB-IoT standard system and development of Internet of things industry were analyzed,which helped readers understand the super impetus of technology development to industry transformation.